Suitability of local materials to purify Akaki Sub-Basin water - Haile Tolera, Habtamu (Karlsruher mineralogische und geochemische Hefte, 2007)
Dissolved and suspended particulate matter (SPM) bound Cu, Zn, Ni, As, Pb, Mn, and Fe are common pollutants in surface and groundwater of the Akaki Sub-Basin.This work (1) presents results of water quality analysis and (2) evaluates an innovative approach for removing heavy metals from polluted water using natural materials. Removal capacities of the filter media for Cu, Zn, Ni, and Pb reach 90%. The main removal mechanisms involved are weak sorption and surface precipitation.